Analisis Karakteristik Arus Lalu Lintas Ditinjau Dari Time Headway Di Jalan Slamet Riyadi Surakarta - IRAWAN, EDY; , Nurul Hidayati, ST., MT., Ph.D; , Drs Gotot Slamet Mulyono, MT (2016)
ABSTRACT Increasing the amount of development in various fields will affect the increase of transportation needs. It can be seen from platoon patterns of traffic flow in the urban roads, including Jl. Slamet Riyadi Surakarta. The parameter used to describe this condition is time headway between two successive vehicles in the traffic flow. This study aims to identify the patterns of platoon that occur in the field, to determine the average headway of any kind of existing pattern, and then to calculate the flow rate of headway based, and then to compare the result with field based. The data used in this study are: traffic flow recording, geometric and environmental conditions including the road network. The pattern of platoon is created by the possibility of the number and types of vehicles that can occur in a selected traffic lane. Based on observation, it can be seen that there are 9 patterns of platoon in the field and it can be grouped as follows: Model 1, MC followed by MC/HV/LV; Model 2, LV followed by LV/MC/HV; and Model 3, HV followed by HV/MC/LV. Based on the analysis, it can be seen that the highest of average headway (2.22 seconds) occurred at 12:05-12:20, while the lowest (1.80) occurred at 10:35-10:50. Derived from the obtained headway, it is found that the highest flow rate is 2028 vehicles/hours and the lowest flow rate is 1619 vehicles/hours. The results of t-test shown that t-stat is 0.873. Because this value is smaller than t-critical then it can be said that there was no significant difference flow rate between headway based and field data based. Keywords: pattern of platoon, headway, flow rate